Hyperthymic affective temperament and hypertension are independent determinants of serum brain-derived neurotrophic factor level. Issue 1 (December 2016) - Nemcsik, János; László, Andrea; Lénárt, Lilla; Eörsi, Dániel; Torzsa, Péter; Kőrösi, Beáta; Cseprekál, Orsolya; Tislér, András; Tabák, Ádám; Gonda, Xenia; Rihmer, Zoltán; Hodrea, Judit; et al.
Abstract Background Brain-derived neurotrophic factor (BDNF) has neuroprotective, proangiogenic and myogenic effects and, therefore, possibly acts as a psychosomatic mediator. Here, we measured serum BDNF (seBDNF) level in hypertensive patients (HT) and healthy controls (CONT) and its relation to affective temperaments, depression and anxiety scales, and arterial stiffness parameters. Methods In this cross-sectional study, affective temperaments, anxiety, and depression were studied with questionnaires (TEMPS-A, HAM-A, and BDI, respectively). SeBDNF level and routine laboratory parameters were measured as well. Arterial stiffness was evaluated with a tonometric method. Results Allover, 151 HT, and 32 CONT subjects were involved in the study. SeBDNF level was significantly higher in HT compared to CONT (24880 ± 8279 vs 21202.6 ± 6045.5 pg/mL, p  < 0.05). In the final model of regression analysis, hyperthymic temperament score (Beta  = 405.8, p  = 0.004) and the presence of hypertension (Beta  = 6121.2, p  = 0.001) were independent determinants of seBDNF. In interaction analysis, it was found that in HT, a unit increase in hyperthymic score was associated with a 533.3 (95 %CI 241.3–825.3) pg/mL higher seBDNF. This interaction was missing in CONT. Conclusions Our results suggest a complex psychosomatic involvement of BDNF in the pathophysiology of hypertension, where hyperthymic affective temperament may have a protective role. BDNF is not likely to have an effect on large arteries.